EXPERIMENTAL EVALUATION OF FLAVONOIDS FROM SOPHORA JAPONICA AS PROSPECTIVE ACTIVE COMPONENTS FOR REGENERATIVE MEDICINE (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background. The identification of bioactive compounds with antioxidant and cytoprotective properties is a key objective of modern regenerative medicine and the development of multifunctional therapeutic agents and biomaterials. Natural flavonoids are of particular interest due to their ability to reduce oxidative stress and create favorable conditions for tissue repair.
Keywords: Sophora japonica; flavonoids; quercetin; rutin; antioxidant activity; cytoprotection; regenerative medicine; wound dressings.